Persistent organochlorine residues in fish and sediments collected from Eastern Aegean coast: Levels, occurrence and ecological risk. Issue 2 (30th June 2017) - Muzyed, Shareef K.I.; Kucuksezgin, Filiz; Tuzmen, Nalan
Abstract: Organochlorines were determined in fish and sediment collected from Izmir and Çandarlı Bays. The results indicated that ΣCyclodiens were generally predominant contaminants. In all samples, p, p ′-DDE was the predominant DDT congener. Aroclors were found in noticeably higher levels than OCPs in sediment and the highest levels of Aroclors, OCPs were found in Nemrut which can be attributed to industrial activities. According to Sediment Quality Guidelines, DDTs were lower than the values that may cause adverse biological risk in sediment samples. Aroclor 1254 in sediments only exceeded the TEL value at Nemrut site. The maximum values of ΣOCPs were found in fish collected from Gülbahçe, while Aroclors were measured in Aliaga. According to related indices, results indicate no recent influxes of DDT in the sampling areas. The estimated daily intake of DDTs, Aroclor1254 were below the acceptable daily intake level recommended by FAO/WHO. Highlights: Cyclodiens were the predominant contaminants in fish and sediment. DDE was the most abundant compound of DDTs. DDTs pose more ecotoxicological concern in sediment from Nemrut site. Aroclor1254 in sediments exceeded the TEL value at Nemrut site. EDI for DDTs in fish species was lower than the ADI recommended by FAO/WHO.